Phase Field Modeling of Anisotropic Tension Failure of Rock-Like Materials - Wang, Susheng; Zhang, Jiuchang; Zhao, Lunyang; Zhang, Wanlu (Frontiers in Physics, 2021)
The tensile fracture is a widespread feature in rock excavation engineering, such as spalling around opened tunnel. Phase filed method (PFD) is a nonlocal theory to simulate effectively the quasi-brittle fracture of materials, especially for the propagation of tensile crack. This work is dedicated to study the tensile failure characteristics of rock-like materials by the PFD simulation of Brazilian test of the intact and fissure disk samples. The numerical results indicate that the tensile strength of disk sample is anisotropic due to the influence of pre-existing cracks. The peak load decreases at first and then increases with the increasing of the inclination angle, following the U-shaped trend. The simulation results also indicate that wing crack growth is the main failure characteristic. Moreover, crack propagation path initiates at the tip of the pre-existing crack when the inclination angle is less than 60°. While crack propagation initiates near the tip of pre-existing crack when the angle is 75° and crack propagation initiates at middle of the pre-existing crack when the angle is 90°. Finally, all cracks extend to the loading position and approximately parallel to the loading direction. This process is agreement with the Brazilian test of pre-existing cracks in laboratory, which can validate the effectiveness of the PFD in simulating the tensile fracture of rock-like materials. This study can provide a reference for fracture mechanism of the surrounding rock in the underground excavation.